2009
DOI: 10.23939/chcht03.04.315
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Structure of Coal Organic Mass. Analytical Review

Abstract: The research works dedicated to the formation regularities of solid fuels chemical structure were analyzed. Modern conceptions of coals chemical structure, which are becoming deeper owing to tooling growth and facts accumulation, were examined by means of critical comparison of different hypothetical models of solid fuels “molecular” structure. The most general points of the respective theories were formulated, according to which “soft” influence on coal structure primary elements bonds system allows bringing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Accordingly to the "guest-master" conception it is necessary to differentiate them as mobile component and "filtering lattice". The same differentiation of coal structural fragments (but in less definite form) is the basis for self-conjunction theory and theory of self-associated multimer [3].…”
Section: Metamorphism "Jumps" Accordingly To Artificial Coalification Datamentioning
confidence: 94%
“…Accordingly to the "guest-master" conception it is necessary to differentiate them as mobile component and "filtering lattice". The same differentiation of coal structural fragments (but in less definite form) is the basis for self-conjunction theory and theory of self-associated multimer [3].…”
Section: Metamorphism "Jumps" Accordingly To Artificial Coalification Datamentioning
confidence: 94%
“…In the works [1,2], an organic coal substance is represented as a collection of packets of condensed aromatic nucleus with side non-aromatic groups including oxygen, nitrogen, sulfur and other heteroatoms that chemically bind the neighboring packets to the spatial polymer. This view suggested that in the course of carbonization in lateral radicals, the carbon-oxygen bonds are replaced by carbon-carbon bonds [3].…”
Section: Introductionmentioning
confidence: 99%